Analisa Potensi Pasar Korea Selatan untuk Produk Kehutanan - Anto Purwanto (Jurnal Syntax Admiration, 2024)
The use of wood as a high-value product does not stop there. Paper, furniture, carbon, and rubber are examples of other non-timber forestry products that are often found in everyday life but are sourced from forests. The purpose of this study is to analyze South Korea's market potential for forestry products. In this study, we use qualitative methodology to understand and evaluate the opportunities and problems faced by Indonesian forestry products, as well as the global market potential for these products. The potential of Indonesian wood commodities and wood products to enter the South Korean market with minimal domestic supply still holds great potential. With abundant supply, offering quality, competitive prices and guaranteeing the required legality documents, it is believed that Indonesia has the opportunity to answer the needs of wood and wood products in the South Korean market in the future.